Public Perceptions of Community Pharmacy-Based Naloxone Services: A National Cross-Sectional Survey - Lindsey A. Hohmann; Zach Krauss; Jitisha Patel; Grace T. Marley (MDPI AG, 2022)
Little is known about the general public's perceptions regarding community pharmacist-delivered naloxone services at the national level. Accordingly, the purpose of this study was to describe the US general public's awareness, knowledge, beliefs, comfort, perceived barriers, abilities, and communication preferences related to community pharmacy-based naloxone services. A national, online cross-sectional survey was conducted in September 2021 among US adults ≥18 years recruited via Amazon Mechanical Turk (MTurk). Primary outcome measures were assessed via 5-point Likert-type scales, including: (1) naloxone awareness and knowledge; (2) naloxone beliefs; (3) comfort with pharmacist-provided naloxone; (4) perceived barriers to pharmacy-based naloxone; (5) opioid overdose competencies, concerns, and readiness; and (6) preferred pharmacist-patient naloxone communication strategy. Analyses included descriptive statistics and logistic regression models to assess predictors of preferred communication strategies. Of 301 respondents, 82.1% were White, 48.8% female, and mean 43 years. Eighty-five percent were unaware of pharmacy-provided naloxone and mean [SD] knowledge score was low (29.3% [16.8]). Mean [SD] beliefs (3.78 [0.61]) and comfort (3.70 [0.54]) were positive, while perceived barriers were low/neutral (2.93 [0.78]). For communication, 54% preferred general advertisement, 32.9% universal offer, and 13.3% targeted offer. The odds of preferring a general advertisement or universal offer over a targeted offer increased with greater awareness (AOR:4.52; p = 0.003) and comfort (AOR:3.79; p = 0.003), and decreased with greater competence (AOR:0.35; p = 0.001). Although awareness and knowledge regarding community pharmacy-based naloxone services was low, beliefs and comfort were positive and perceived barriers were low/neutral. General or universal offers of naloxone were preferred over targeted approaches. Future studies should test the impact of communication strategies on naloxone uptake.